Heat waves over Andhra Pradesh : A case study of summer 2003 - BHADRAM, C. V. V.; AMATYA, B. V. S.; PANT, G. B.; KUMAR, K. KRISHNA (MAUSAM, 2005)
Temperature data of pre-monsoon months for major stations in Andhra Pradesh for long period (1901-2002) have been analysed to identify the variations in maximum temperature. Analysis of short period temperature data (1986-2002) has shown increase in the frequency of severe heat waves and also duration of heat wave spells during the last decade. Since the severe heat waves during May-June 2003 over Andhra Pradesh have claimed many lives, a detailed study of all meteorological parameters associated with such heat waves has been made and the results are discussed. Human comfort indices - Heat Index (HI), Thom’s Discomfort Index & Webbs’ Comfort Index computed in respect of coastal stations have clearly reflected the severity of heat waves.